Otitis externa in general practice. Issue 2 (February 2023) - Dolan, Sean; Ellis, Sarah
Otitis externa is a common condition encountered in primary care, with 10% of the population being affected during their lifetime. It can cause many patient issues including pain, sleep disturbance, hearing loss and temporary loss of income. It can have a significant burden on patients' mental health and psychosocial wellbeing.